Повышение качества порошков карбида вольфрама - Богатырева, Г.П.; Ильницкая, Г.Д.; Петасюк, Г.А.; Сирота, Ю.В.; Лысаковский, В.С.; Закора, Е.А.; Грищенко, Г.С.; Жудра, А.П.; Белый, А.И.; Дзыкович, В.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The results division powders of carbide tungsten under the form of particles and allocation from a total mass of particles carbide tungsten of not spherical and extended form are presented in this report. After division of powders carbide tungsten of various grain sizes 630/800, 450/630, 250/450, –250 microns and –180 microns on vibrating installation under the form of particles are received the powders differing among themselves under morphological characteristics.